(untitled) (CIPEEX, 2025)
Hematology is the specialty that studies blood and its components, essential for the diagnosis and treatment of various diseases. Blood donation is a voluntary act that saves lives, but requires rigorous care to ensure the safety of both donor and recipient. This summary aims to highlight the importance of blood donation, the associated risks, the necessary care in handling, and the pharmacist’s responsibility in this process. A bibliographic analysis of scientific articles and health guidelines on hematological practices, donation protocols, and pharmaceutical practice in blood centers and hospitals was conducted. Blood donation is essential in emergency situations, surgeries, and hematological treatments. However, diseases such as HIV, hepatitis B and C, syphilis, and Chagas disease can be transmitted without adequate screening. Safe handling includes serological testing, temperature control, proper storage, and bag traceability. Pharmacists, as qualified professionals, ensure the quality of supplies, validate processes, guide staff, and educate donors. Their ethical and technical responsibilities directly contribute to transfusion safety and risk prevention. Blood donation is one of the main pillars of public health, and its success depends on safe practices and trained professionals. Pharmacists play a strategic role in the blood supply chain, ensuring that each stage from collection to clinical use is carried out with excellence and responsibility. Raising awareness of the importance of blood banks and continuously improving professionals and services are essential to strengthening public confidence in the role of pharmacists in hematology, as well as ensuring the desired therapeutic efficacy.